British Stock Market, BREXIT and Media Sentiments - A Big Data Analysis - Gopal K. Basak; Pranab Kumar Das; Sugata Marjit; Debashis Mukherjee; Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper we show, using a Machine Learning Framework and utilising a substantial corpus of media articles on Brexit, confirmed evidence of co-integration and causality between the ensuing media sentiments and British currency. The novel contribution of this paper is that along with sentiment analysis using commonly used lexicons, we devised a method using Bayesian learning to create a more context aware and more informative lexicon for Brexit. Moreover, leveraging and extending this we can unearth hidden relationship between originating media sentiments and related economic and financial variables. Our method is a distinct improvement over the existing ones and can predict out of sample outcomes better than conventional ones.
Keywords: 330; digitization; machine learning